PENGARUH SPIRITUALITAS DI TEMPAT KERJA TERHADAP TURNOVER INTENTION MELALUI KOMITMEN ORGANISASI - Inkai Y, Dita; Kistyanto, Anang (Fakultas Ekonomi, UIN Maliki Malang, 2013)
The aims of research are to examine and to analyze whether workplace spirituality to turnover intention through the organizational commitment (the study of the employee non-nurse medical directorate RS. Al â€“ Irsyad Surabaya). The sampling technique of research used proportionate stratified random sampling, with 86 respondents as sample. Statistical analysis method used partial least square (PLS). Based on causality test, showed that spirituality in the workplace has positive and significant on the organizational commitment.Â Organizational commitment has negative and significant on the turnover intention. The value of the coefficient indirect effect of spirituality in the workplace against turnover intention through organizational commitment is greater than the direct effect of spirituality in the workplace against turnover intention. The result that organizational commitment as mediation of spirituality in the workplace to turnover intention.